Analisis Kelelahan Dan Beban Kerja Menggunakan Subjective Self Rating Test Dan NASA-TLX - Nurmarifah, Atun; Lahay, Idham Halid; Sunardi (Universitas Negeri Gorontalo, 2024)
The application of ergonomics in the workplace is one concept that can be done to provide comfort and safety to workers when doing work. This research was conducted on UD workers. Arafat Meubel which is a furniture manufacturing factory. The problem for workers is the number of targets from the company, which causes working time outside the normal working limits and makes workers experience fatigue and excessive workload. This study aims to analyze the level of fatigue and mental workload of workers, and determine the relationship between the two. The methods used are Subjective Self Rating Test to determine the level of fatigue and Nasa-Tlx to determine the level of mental workload, and using the Spearman Rank Test to determine the relationship between fatigue and mental workload. The results obtained from data processing and analysis were that 2 workers experienced high levels of fatigue and 5 workers experienced high levels of mental workload. In addition, there is a relationship between fatigue and mental workload with a correlation coefficient of 0.559, including in the medium relationship category.